Cytotoxicity, Intracellular Replication, and Contact-Dependent Pore Formation of Genotyped Environmental Legionella pneumophila Isolates from Hospital Water Systems in the West Bank, Palestine - Zayed, Ashraf R. (Pathogens, 2021)
Legionella pneumophila is the causative agent of Legionnaires’ disease. Due to the hot climate and intermittent water supply, the West Bank, Palestine, can be considered a high-risk area for this often fatal atypical pneumonia. L. pneumophila occurs in biofilms of natural and man-made freshwater environments, where it infects and replicates intracellularly within protozoa. To correlate the genetic diversity of the bacteria in the environment with their virulence properties for protozoan and mammalian host cells, 60 genotyped isolates from hospital water systems in the West Bank were analyzed. The L. pneumophila isolates were previously genotyped by high resolution Multi Locus Variable Number of Tandem Repeat Analysis (MLVA-8(12)) and sorted according to their relationship in clonal complexes (VACC). Strains of relevant genotypes and VACCs were compared according to their capacity to infect Acanthamoeba castellanii and THP-1 macrophages, and to mediate pore-forming cytotoxicity in sheep red blood cells (sRBCs). Based on a previous detailed analysis of the biogeographic distribution and abundance of the MLVA-8(12)-genotypes, the focus of the study was on the most abundant L. pneumophila- genotypes Gt4(17), Gt6 (18) and Gt10(93) and the four relevant clonal complexes [VACC1, VACC2, VACC5 and VACC11]. The highly abundant genotypes Gt4(17) and Gt6(18) are affiliated with VACC1 and sequence type (ST)1 (comprising L. pneumophila str. Paris), and displayed seroroup (Sg)1. Isolates of these two genotypes exhibited significantly higher virulence potentials compared to other genotypes and clonal complexes in the West Bank. Endemic for the West Bank was the clonal complex VACC11 (affiliated with ST461) represented by three relevant genotypes that all displayed Sg6. These genotypes unique for the West Bank showed a lower infectivity and cytotoxicity compared to all other clonal complexes and their affiliated genotypes. Interestingly, the L. pneumophila serotypes ST1 and ST461 were previously identified by in situ-sequence based typing (SBT) as main causative agents of Legionnaires’ disease (LD) in the West Bank at a comparable level. Overall, this study demonstrates the site-specific regional diversity of L. pneumophila genotypes in the West Bank and suggests that a combination of MLVA, cellular infection assays and hierarchical agglomerative cluster analysis allows an improved genotype-based risk assessment.